Levelling the playing field for the international migration of nurses: the India English Language Programme - Ross Goldstone; Rose McCarthy; Ged Byrne; David Keen (BMC, 2023)
Abstract Background This article presents evaluation findings of the India English Language Programme, an innovative programme aimed at providing Indian nurses with an opportunity to participate in an ethical and mutually beneficial learning programme aimed at supporting migration into the United Kingdom's National Health Service (NHS). The programme provided 249 Indian nurses wishing to migrate to the NHS on an 'earn, learn, and return' basis with funding to support English language learning and accreditation sufficient to apply for Nursing and Midwifery Council (NMC) registration. The Programme provided English language training and pastoral support to candidates, in addition to the availability of remedial training and examination entry for those not meeting NMC proficiency requirements on their first attempt. Methods Descriptive statistical analysis of programme examination results and cost-effectiveness analysis is presented to demonstrate programme outputs and outcomes. Descriptive economic analysis of programme costings is presented alongside programme results to investigate the value-for-money provided by this programme. Results A total of 89 nurses were successful in meeting NMC proficiency requirements, representing a pass rate of 40%. Those undertaking OET training and examination(s) were more successful, compared to those undertaking British Council provision, with over half of candidates passing at the required level. This equates to an overall programme cost-per-pass of £4139 and represents a model to support health worker migration, in line with WHO guidelines, delivering individual learning and development, mutual health system gain, and value-for-money. Conclusions Taking place during the coronavirus pandemic, the programme evidences the effective delivery of online English language training to support health worker migration during a highly disruptive period for global health. This programme demonstrates an ethical and mutually beneficial pathway for English language improvement amongst internationally educated nurses to facilitate migration to and global health learning in the NHS. It provides a template through which healthcare leaders and nurse educators, working in policy and practice environments in the NHS and other English-speaking countries, can design future ethical health worker migration and training programmes to strengthen the global healthcare workforce.